The usefulness of immunohistochemistry to differentiate between nasal carcinoma and lymphoma in cats: 140 cases (1986–2000). (23rd April 2012) - Nagata, K.; Lamb, M.; Goldschmidt, M. H.; Duda, L.; Walton, R. M.
Abstract A retrospective evaluation of 232 feline nasal biopsies initially diagnosed as either carcinoma or lymphoma was performed by two pathologists. One or both pathologists disagreed with the original diagnosis in 15 cases (7%), 14 of which had original diagnoses of carcinoma. Out of the 232 cases, 140, including the disputed ones, were subjected to immunohistochemical staining with epithelial and lymphoid markers. Immunohistochemical staining of the 15 disputed cases showed that the original diagnoses were incorrect in 67% (10/15), unverified in 13% (2/15) and correct in 20% (3/15). Among the consensual diagnoses, immunohistochemistry revealed that 3% (4/125) of diagnoses were unverified because they did not stain for any of the markers evaluated. This report demonstrates the importance of immunohistochemistry in establishing a correct histologic diagnosis for nasal neoplasms in cats.